High Quality MoSe2 Nanospheres with Superior Electrochemical Properties for Sodium Batteries. Issue 8 (2nd June 2016) - Wang, Hui; Wang, Li; Wang, Xiaoyan; Quan, Junjie; Mi, Longfei; Yuan, Lan; Li, Guopeng; Zhang, Bin; Zhong, Honghai; Jiang, Yang
Abstract : Highly ordered MoSe2 nanospheres are successfully fabricated via a facile colloidal route. The unique as-obtained MoSe2 nanospheres render the high-rate transporation of sodium ion due to small size and high specific surface area. As the anode, MoSe2 nanospheres yield the initial discharge/charge capacities of 520/430 mAh g −1 for potentials ranging from 0.1 to 3 V at a current rate of 0.1 C with an 80% capacity retention over 200 cycles. In addition, MoSe2 nanospheres also demonstrate excellent electrochemical performance at high current densities. Using first-principles simulation, the activation barriers for sodium ion transportation on the surface as well as interlayer of the MoSe2 are 0.344/1.31 eV respectively, suggesting that high specific surface area MoSe2 nanospheres can serve as an attractive anode material for Na ion batteries.